Preparation and Evaluation Aspects of Herbal Kajal (International Journal of Scientific Research in Science and Technology, 2024)
Traditionally, kajal is designed as a cosmetic product for enhancing the beauty of eyes and also as a medicinal product to treat eye ailments such as irritation, eye inflammation, redness, dryness etc. Kajal is mostly in the form of paste and sometimes in cake form, which is modified as sticks for easy application. They are prepared using soot of oils and herbs. The kajal is evaluated by different parameters like such as physical description, pH, viscosity, spreadability, stability studies, evaluation of bases, TLC of extracts and in-vitro studies. The present study covers the various aspects of Kajal prepared by various researchers which are published in various platforms. In the present study, formulation and evaluation of 4 different kajal are also reported. The results of which revealed that the materials and methods used plays important role in the quality of product as it is important to evaluate kajal for its quality, efficacy, stability and safety. Thus, this paper will be beneficial for those who are working for the standardization of medicinal and cosmetic products like Kajal.